2013
DOI: 10.1063/1.4811872
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensionality in fluidized nanopowder agglomerates

Abstract: Abstract. In recent years, the interest in fluidization as a mean to process nanoparticles is strongly increasing. Due to the small size of the nanoparticles, which makes van der Waals forces predominate, they do not fluidize as single particles but as agglomerates. Various researchers using settling experiments and bed expansion measurements conclude that fluidized agglomerates are fractal structures with a single fractal dimension of 2.5. Based on microscopy results, Wang et al. "Powder Technology 124, 152-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The estimation of the theoretical polarization requires knowledge on the density–density correlation function for the sample, the projection of the density–density correlation function in the form of an Abel transform, and the solid fraction of the sample. A detailed description of the SESANS data analysis can be found in the publications by de Martin et al , and Andersson et al , …”
Section: Discussionmentioning
confidence: 99%
“…The estimation of the theoretical polarization requires knowledge on the density–density correlation function for the sample, the projection of the density–density correlation function in the form of an Abel transform, and the solid fraction of the sample. A detailed description of the SESANS data analysis can be found in the publications by de Martin et al , and Andersson et al , …”
Section: Discussionmentioning
confidence: 99%
“…For nanoparticles, it was found that agglomeration takes place in distinctive steps: primary particles to aggregates (sometimes called sub‐agglomerates) to primary or simple agglomerates to complex agglomerates, which is a phenomenon that was discovered by Yao et al [ 33 ] Each stage of the multi‐stage agglomeration (MSA) has its own density and fractal dimension. [ 139 ] The latter is a more recent insight since a fractal dimension of 2.5 was earlier used for all stages of nanoparticle agglomeration. [ 115,140,141 ] No MSA has been described for microparticles, making the final agglomerates present in the fluidized bed of microparticles significantly different.…”
Section: Modelling Agglomerationmentioning
confidence: 99%